Three dimensional non-isentropic subsonic Euler flows in rectangular nozzles. (February 2015) - Chen, Chao
Abstract: In this paper, we study the existence and uniqueness of three dimensional non-isentropic subsonic Euler flows in rectangular nozzles. This work is an extension of Chen and Xie's work on isentropic subsonic Euler flows. If, besides small normal component of vorticity, Bernoulli's function and entropy function with small variations are given on the entrance, the existence and uniqueness of non-isentropic subsonic Euler flows are established.